Drugs, violence, and trauma in Mexico and the USA (2017)
The impact of illicit drug markets on the occurrence of violence varies tremendously depending on many factors. Over the last years, Mexico and the USA have increased security border issues that included many aspects of drug-related trade and criminal activities. Mexico experienced only a small reduction in trauma deaths after the enforcement of severe crime reinforcement policies. This strategy in the war on drugs is shifting the drug market to other Central American countries. This phenomenon is called the ballooning effect, whereby the pressure to control illicit drug-related activities in one particular area forces a shift to other more vulnerable areas that leads to an increase in crime and violence. A human rights crisis characterized by suffering, injury, and death related to drug trafficking continues to expand, resulting in the exorbitant loss of lives and cost in productivity across the continent. The current climate of social violence in Central America and the illegal immigration to the USA may be partially related to this phenomenon of drug trafficking, gang violence, and crime. A health care initiative as an alternative to the current war approach may be one of the interventions needed to reduce this crisis.